2014
DOI: 10.1039/c4an01147c
|View full text |Cite
|
Sign up to set email alerts
|

Modification of microfluidic paper-based devices with silica nanoparticles

Abstract: This paper describes a silica nanoparticle-modified microfluidic paper-based analytical device (μPAD) with improved color intensity and uniformity for three different enzymatic reactions with clinical relevance (lactate, glucose, and glutamate). The μPADs were produced on Whatman grade 1 filter paper and using a CO2 laser engraver. Silica nanoparticles modified with 3-aminopropyltriethoxysilane (APTES) were then added to the paper devices to facilitate the adsorption of selected enzymes and prevent the washing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 67 publications
2
96
0
Order By: Relevance
“…The latter methodology allows calculating not only the adsorbed amount but also the adsorption rate, which could be then used to calculate the probability of attachment for a protein under specific experimental conditions [120-122]. Among other techniques[123-126] that have been applied, adsorption kinetics of proteins can be investigated using quartz crystal microbalance (QCM)[92, 127-130] orellipsometry[131, 132].…”
Section: Techniques To Investigate Protein Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter methodology allows calculating not only the adsorbed amount but also the adsorption rate, which could be then used to calculate the probability of attachment for a protein under specific experimental conditions [120-122]. Among other techniques[123-126] that have been applied, adsorption kinetics of proteins can be investigated using quartz crystal microbalance (QCM)[92, 127-130] orellipsometry[131, 132].…”
Section: Techniques To Investigate Protein Adsorptionmentioning
confidence: 99%
“…The nanoparticles were used to immobilize the protein to the paper and a 61% increase in color intensity was observed when the nanoparticles were incorporated into the device versus native paper [122]. A novel glutamate amperometric biosensor was made through the assembly of PtNP on modified ordered three-dimensional gold nanowire arrays[260].…”
Section: Adsorbedproteinsmentioning
confidence: 99%
“…45 Likewise, Chen and Wu 46 demonstrated that by creating a conjugate with multiple fluorescent dyes, the limit of detection for Cry1Ab-a type of toxic insecticidal protein in genetically modified organismscould be significantly reduced. Other groups have similarly constructed conjugates for signal amplification to improve the limit of detection of analytes 47,48 or improve uniformity of colorimetric readouts. 48 Besides amplifying the signal of test lines produced from gold nanoparticles, research is also being conducted to find other detector probes that are more sensitive than gold nanoparticles to further lower the detection limit.…”
Section: Signal Amplificationmentioning
confidence: 99%
“…Other groups have similarly constructed conjugates for signal amplification to improve the limit of detection of analytes 47,48 or improve uniformity of colorimetric readouts. 48 Besides amplifying the signal of test lines produced from gold nanoparticles, research is also being conducted to find other detector probes that are more sensitive than gold nanoparticles to further lower the detection limit. Other metallic nanoparticles have similar properties to gold nanoparticles and thus can also be used for LFA tests.…”
Section: Signal Amplificationmentioning
confidence: 99%
“…Figure 4 provides an example of a fabrication procedure of a microfluidic paper-based analytical devices (μPADs) that involved treatment of the paper chip with a nanomaterial colloidal solution of Fe3O4NPs, MWCNT and graphene oxide (GO) to create a biocompatible layer with high catalytic activity. 47 Evans et al 48 modified μPADs with SiO2NPs to improve color intensity and uniformity of a colorimetric device applied to three different enzymatic reactions with clinical relevance (lactate, glucose, and glutamate). Sharpe et al developed novel chemical sensing arrays based on redox active metal oxide NPs as a portable and inexpensive paper-based colorimetric method for polyphenol detection 49 and field characterization of antioxidant containing samples 27 ( Fig.…”
Section: ·2 Modification Of Cellulose Papermentioning
confidence: 99%